Muslim estate administration: the locus of Malaysian Syariah Court in Malaysia - Muhamad Helmi Md Said,; Muhammad Amrullah Drs Nasrul,; Nora Abdul Hak Ahmad,; Wan Noraini Mohd Salim, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The concept of dual justice system practiced in Malaysia governs the area of inheritance where there is a notable difference between Muslim and non-Muslim estate administration. While the non-Muslims deal solely with civil court, the Muslims are governed under both civil and Syariah Court. For Muslims, reference to Syariah Court is required for the purpose of obtaining the fara’id certificate, prior to the application to other administrative bodies. Having to deal with multiple bodies tends to lead to a confusion among the Muslims as to which institution should they approach, signifying the extra commitment that they will have to make. The complexity of the process encountered by the beneficiary results in discouragement to proceed the administration which eventually led to delay in estate administration and distribution. The lack of understanding regarding the function of the Syariah Court holds as a key factor to this ongoing issue. This paper adopts the library-based research which focuses on the analysis of written sources including but not being limited to journal articles, statutes, case laws and text books. In its findings, this paper states that there is a need for the government to re-look into the structure of the administrative bodies by making proper amendments in order to simplify the current process of the Muslim estate administration.